On a stress state of orthotropic plane with absolutely rigid inclusion - V. Hakobyan; L. Dashtoyan (National Academy of Sciences of Armenia)
Drawing on the discontinuous solutions of the elasticity theory for orthotropic plane, the study purports to offer exact solutions to mixed boundary value problems for orthotropic plane with absolutely rigid thin inclusion on one of the major directions, when one edge of it is wholly coupled with plane and the other side is in contact with plane under the condition of Coulomb friction.
Keywords: Physics; Mechanics of deformable solids